Acne: An Ignored Dermal Malady - Kapoor, Dr. Anupriya (Asian Journal of Pharmaceutics (AJP), 2022)
Acne vulgaris is a dermal inflammatory condition that originates as a result of clogging of the pilosebaceous unit and is a complicated skin ailment that affects over 85% of young people around the world. The disorder has a crucial impact on a patient’s life quality. The causative bacterium for acne is Propionibacterium acne. The article emphasizes on the prime factors responsible for the occurrence of acne and also highlights the various forms of acne, types of scars and clinical diagnosis for the same. Various options for the management of acne including topical agents, oral antibiotics, and therapies along with preventive methods are discussed in the article.